The Effect of Scaffolding Strategies on Learning Outcomes in Science Learning: A Systematic Literature Review - Cantik Azzaroiha; I Wayan Redhana; Ketut Suma (Jurnal Penelitian Pendidikan IPA, 2025)
Science learning must be designed so that students can understand natural phenomena that are constantly changing. This study aims to explore scaffolding strategies related to research trends, influence on learning outcomes, appropriate learning models, research designs used, and profiles of the use of scaffolding in science learning at various levels of education. The research is a systematic literature review (SLR) to collect, analyze, and compile findings on scaffolding strategies in science learning. The literature review results show that scaffolding strategies are effective in helping students understand scientific concepts better. Providing structured scaffolding to students effectively improves students’ learning outcomes. The literature review results show that in the 2014-2024 time span, research on the application of scaffolding mostly uses quantitative methods with a non-equivalent control group design. The learning model that is widely used with scaffolding is Problem-Based Learning (PBL). Scaffolding positively impacts students' cognitive and affective learning outcomes, concept understanding, science process skills, argumentation skills, critical thinking skills, higher-order thinking skills (HOTS), learning independence, learning motivation, scientific literacy, problem-solving skills, and misconceptions. The scaffolding strategies can improve science learning effectively.